Stability of carbon and nitrogen isotopic compositions of the protein extracted from milk and their potential as "fingerprints" of geographical origin. Issue 31 (29th March 2017) - Dong, Hao; Xiao, Kaijun; Luo, Donghui
Abstract : The present work aimed to determine whether isotopic compositions can be used as "fingerprints" in identifying the geographical origin of milk. Abstract : The present work aimed to determine whether isotopic compositions can be used as "fingerprints" in identifying the geographical origin of milk. For this purpose, δ 13 C and δ 15 N values of the proteins extracted from fifty-six Tetra Pak milk samples originating from four continents, including Australia (with New Zealand), Europe (Germany and France), North America (the United States) and Asia (China), were determined using elemental analyzer-isotope ratio mass spectrometry (EA-IRMS). The effects of storage time and temperature on the δ 13 C and δ 15 N values were also studied in order to evaluate the stability of the isotopic composition and hence the ability of the developed EA-IRMS method to identify the geographical origin of milk. The results indicated that there were no significant differences ( P > 0.05) for δ 13 C and δ 15 N values for the samples stored under different conditions, demonstrating the stability of the isotopic compositions in the proteins extracted from these milk samples. The δ 13 C values of these extracted proteins ranged from −29.36‰ to −15.02‰. Their mean δ 15 N values were calculated to be between 4.55‰ and 5.80‰, with the highest, second-highest, third-highest, and lowest values for the samples from Australia (with New Zealand), Europe, America, and Asia, respectively. Significant differences ( P < 0.05) were found in the δ 13 C and δ 15 N values between these four regions, verifying their potential as "fingerprints" of the geographical origin of milk. The results obtained confirm the suitability and potential of stable isotopic composition ( δ 13 C and δ 15 N) analysis in determining the geographical origin of milk.